2010 6th International Conference on Wireless and Mobile Communications 2010
DOI: 10.1109/icwmc.2010.104
|View full text |Cite
|
Sign up to set email alerts
|

A Cost Effective Real-Time Tracking System Prototype Using Integrated GPS/GPRS Module

Abstract: This paper presents a real time tracking system that provides accurate localizations of the tracked vehicle with low cost. The system is implemented using GM862 cellular quad band module. A monitoring server and a graphical user interface on a website have also been implemented using Microsoft SQL Server 2003 and ASP.net to view the current location of a vehicle on a specific map. The system provides information regarding the vehicle status such as speed, mileage. The prototype has been tested experimentally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…These proofs will support the Police Department, Traffic Department, Road Transport Department while the investigation of accident cases with clear data proofs such that the justice can be done for the right person. The data collected by the data logger also supports with the clear data of the violations of traffic with proper indications [1][2][3].…”
Section: Introductionsupporting
confidence: 61%
“…These proofs will support the Police Department, Traffic Department, Road Transport Department while the investigation of accident cases with clear data proofs such that the justice can be done for the right person. The data collected by the data logger also supports with the clear data of the violations of traffic with proper indications [1][2][3].…”
Section: Introductionsupporting
confidence: 61%
“…In [16] error sources in GPS measurement are calculated. In [17] development of real-time visual tracking system for vehicle safety applications is discussed and the concept of focus of expansion (FOE) is introduced. A low cost real time tracking system that provides accurate localizations of the tracked vehicle is presented in [18].Vehicle tracking coupled with vehicle registration number recognition is introduced in [19].…”
Section: Survey Of Related Researchmentioning
confidence: 99%
“…Verma et al showed the user that it was possible to follow the travelled route and position of the vehicle through GPS and showed the position of the vehicle using a web based system which that had developed [3]. Using Microsoft SQL Server 2003, El-Medany et al, developed a monitoring system, established graphical user interface using Active Server Pages (ASP) and showed the position of the vehicle on the map [4]. Fleischer, P.,B.…”
Section: Introductionmentioning
confidence: 98%